Local Scour Process in Conduit Aerated Water Jets - Tuna, M. Cihat; Acar, Ramazan; Tunç, Mustafa (Springer Basel Ag, 2026)
High-velocity water jets emerging from hydraulic structures cause local scouring in downstream areas, creating significant risks to structural safety. In this study, the effects of natural aeration provided through pressurized pipes on jet-induced scouring were investigated through laboratory experiments. A total of 60 experiments were conducted for different gate openings, flow rates, and downstream water levels; the scour geometries created by aerated and non-aerated jets were compared. The aeration level was defined by the dimensionless air-to-water flow ratio (Qa/Qw); maximum scour depth, scour length, scour slope angle, and jet fall distance were considered as basic evaluation parameters. The experimental results showed that increased aeration significantly reduced the maximum scour depth and scour length while moving the point of contact of the jet further upstream. While the scour depth and slope angles reached their highest values in non-aerated jets, shallower and flatter scour profiles were formed in aerated conditions. An empirical relationship predicting the maximum scour depth using experimental data has been developed and found to be in high correlation with the measured values (R2 = 0.93). The findings reveal that channel aeration is an effective method for reducing scouring and demonstrate that this approach can be considered a safe and economical alternative in the design of spillways, wastewater treatment plants, and similar hydraulic systems.
Keywords: Aeration; air/water flow; scour hole; conduit; Froude number